An Observational Prospective Cohort Study of Vaccine Effectiveness Against Severe Acute Respiratory Syndrome Coronavirus 2 Infection of an Aerosolized, Inhaled Adenovirus Type 5–Vectored Coronavirus Disease 2019 Vaccine Given as a Second Booster Dose in Guangzhou City, China - Wang, Fu-Zhen; Zhang, Chun-Huan; Tang, Lin; Rodewald, Lance E; Wang, Wen; Liu, Si-Yu; Wang, Wen-Ji; Wu, Dan; Liu, Qian-Qian; Wang, Xiao-Qi; Huang, Li-Fang; Huang, Ao-Di; et al. (The Journal of infectious diseases, 2024)
Abstract Using a prospective, observational cohort study during the post–“dynamic COVID-zero” wave in China, we estimated short-term relative effectiveness against Omicron BA.5 infection of inhaled aerosolized adenovirus type 5–vectored ancestral strain coronavirus disease 2019 (COVID-19) vaccine as a second booster dose approximately 1 year after homologous boosted primary series of inactivated COVID-19 vaccine compared with no second booster. Participants reported nucleic acid or antigen test results weekly until they tested positive or completed predesignated follow-up. After excluding participants infected <14 days after study entry, relative effectiveness among the 6576 participants was 61% in 18- to 59-year-olds and 38% in ≥60-year-olds and was sustained for 12 weeks. In a real-world study during China's large SARS-CoV-2 BA.5 variant epidemic wave, effectiveness against actively monitored infection of an inhaled adenovirus type 5–vectored COVID-19 vaccine was 61% in 18- to 59-year-olds and 38% in ≥60-year-olds and was sustained for 12 weeks.